Benefits Management in University-Industry R&D collaborative projects: a review on benefits and success factors - Andrade, Rita (2016)
"Conference on ENTERprise Information Systems / International Conference on Project MANagement / Conference on Health and Social Care Information Systems and Technologies, CENTERIS / ProjMAN / HCist 2016"